POTENSI FLAVONOID BIJI ADAS (Foeniculum vulgare Mill) SEBAGAI ANTIANEMIA - Erinda Nur Pratiwi (Universitas Muhammadiyah Klaten, 2026)
Anemia is a common disease worldwide, especially in developing countries. In adults, anemia occurs in women of childbearing age, especially pregnant and breastfeeding women because they often experience iron deficiency. Overall, anemia occurs in 45% of women in developing countries and 13% in developed countries. According to the World Health Organization (WHO), anemia in pregnancy is defined as a hemoglobin level of less than 11 g/dl. The pathophysiology of iron deficiency anemia (IDA) is caused by a disruption in iron homeostasis in the body. If iron stores in the bone marrow are reduced, the erythropoiesis process will be disrupted, resulting in disruption of erythrocyte formation, this indicates IDA. Iron binding and erythrocyte activity will induce the hormone erythropoietin (EPO) in the kidneys, which affects bone marrow activity in iron stores. Fennel seeds (Foeniculum vulgare Mill) contain various flavonoid compounds that can improve iron deficiency anemia. This study aims to prove the potential of flavonoids from fennel seeds as an antianemia therapy through an in-silico approach. This study used AutoDockTools 1.5.6. The materials used included two-dimensional structures of flavonoid test compounds that had been drawn and optimized with VegaZZ. The crystallized structures of target macromolecules, namely EPO, Hepcidin, TIBC, and erythrocytes, were obtained from the Protein Data Bank website. A toxicity prediction test was used to detect the toxicity level of flavonoid compounds in fennel seeds.